The Rights of Indigenous Law Communities in Forest Management in the West Seram Regency: A Perspective of National and Customary Law - E.M., Nirahua Salmon; Nirahua, Garciano; Soplantila, Ronny (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
Recognition of indigenous legal communities as legal subjects with rights over their territories and natural resources is a constitutional mandate, as stipulated in Article 18B, paragraph (2) of the 1945 Constitution of the Republic of Indonesia. In West Seram Regency, indigenous legal communities have a traditional governmental structure that manages customary forests as part of the territorial domains. This article aims to analyze the implementation of the rights of indigenous legal communities in forest management from a constitutional perspective and local practices. The research method used is a juridical-empirical approach with data collection techniques through literature study and interviews with local leaders and regional officials. The research findings indicate that although there is a normative recognition of the rights of indigenous peoples, the implementation at the local level, especially in West Seram Regency, still faces regulatory, administrative, and political obstacles. This causes the legal status of customary forests to be unclear and vulnerable to overlap with state claims or corporate permits. Therefore, affirmative steps are needed from local governments through regional regulations and collaborative programs that strengthen the position of indigenous communities as key actors in the management of forests based on local wisdom. The local wisdom of customary law communities, accumulated throughout the history of the development of customary law communities, plays a significant role for the customary law communities and their rights, including communal land rights both in marine and terrestrial areas.Â